Workshop tpack dalam pembelajaran sebagai upaya meningkatkan keterampilan guru tingkat SMP - Rochmat Tri Sudrajat; Dida Firmansyah (Abdimas Siliwangi, 2022)
Education is a significant component in human development both in formal, informal, and non-formal education. Education and learning continue developing and evolving according to the times and technology. The service focuses on the impact of TPACK training on junior high school teachers to have a positive effect, increasing the creativity and ability of teachers to master renewable technology in the learning process. The servant uses a descriptive method with triggering training scenarios that have been designed and adapted to the learning materials at the junior high school level. The results of the treatment in the form of workshops for teachers at the junior high school level were very significant, it was concluded from several instruments used as a tool for measuring the treatment process to evaluating the impact on service participants.